Influence of Process on the Formation of Main Taste Substances and Quality of Chuanhong Congou Black Tea - Jing HU; Bo DUAN; Zhiwei HE; Lei LIAO; Jiahui DU; Na LIU; Gang CHENG; Yang YE (Shipin gongye ke-ji)
Sensory evaluation combined with high-performance liquid chromatography (HPLC) and amino acid analysis were used to study the effects of withering, rolling, fermentation, and drying (first-drying and sencod-drying) on the main taste substances and their quality formation using one bud and one leaf of Sichuan group species as raw materials. Results showed that the taste intensity profiles of tea samples obtained from different processing procedures differed significantly. During the process of Chuanhong congou black tea, the intensity of sour, salty, and bitter gradually decreased, while the intensity of sweetness gradually increased. The umami intensity increased significantly (P<0.05) during the first-drying process, however, overall it still showed a downward trend. The stage of withering had the most significant effect on amino acids. The content of all amino acids, except for GABA, valine, lysine, and tyrosine, remained at the highest level during this stage. During the rolling and fermentation stages, most of the catechins, especially the ester catechins EGCG, ECG, EC, and EGC, decreased by 90%. Amino acids also decreased significantly, while theaflavins increased significantly (P<0.05). The drying process resulted in an increase in the theaflavins and a decrease in most of the amino acids and catechins. However, the change in caffeine content was not significant. Additionally, the flavour composition was altered, resulting in a reduction in the intensity of sour, salty, and bitter flavours in the tea solution, and an increase in the intensity of sweetness. The results provided a theoretical basis for the targeted improvement of Chuanhong congou black tea quality by regulating the process.